Romeo and Juliet beyond words - Prokofʹev, Sergej Sergeevič 1891-1953 (Opus Arte, 2019)
"Romeo and Juliet : Beyond Words is a ballet feature film created by the International Emmy Award-winning Michael Nunn and William Trevitt. It stars the dancers of The Royal Ballet in Kenneth MacMillan's classic ballet and is set to Sergei Prokofiev's original score. Highlighting the essence of MacMillan's world-renowned choreography, Nunn and Trevitt's Romeo and Juliet takes us into the action with striking intimacy. Through detailed portrayals by The Royal Ballet dancers, we experience Shakespeare's iconic characters in a new and intimate way, and this groundbreaking film captures the kind of extraordinary performances that have earned The Royal Ballet their world-class reputation. Filmed on location, Nunn and Trevitt's Romeo and Juliet has been re-imagined for the camera, in a production that is internationally recognized as being at the zenith of dance storytelling. This is a story everyone knows, told in the universal language of dance, presented in a way never seen before."--Container
Originally produced as a motion picture in 2019
Wide screen (1.78:1)
Extra features : Making of Romeo and Juliet -- Romeo and Juliet : Q&A with the cast and crew -- Cast gallery
William Bracewell, Francesca Hayward, Matthew Ball, Marcelino Sambé, James Hay, Kristen McNalky, Christopher Saunders, Romany Pajdak, Tomas Mock, Bennet Gartside, Tierney Heap, Laura Morera, Beatriz Stix-Brunell
Choreography, Kenneth MacMillan; score, Sergei Prokofiev; costume design, Nicholas Georgiadis ; photography by William Trevitt ; editor Jimmy Piper ; score performed by The Orchestra of the Royal Opera House, conductor Koen Kessels
Keywords: Shakespeare, William / 1564-1616 / Adaptations; Romeo / (Fictitious character) / Drama; Juliet / (Fictitious character) / Drama; Verona (Italy) / Drama; Vendetta / Drama; Youth / Drama; Juliet / (Fictitious character); Romeo / (Fictitious character); Shakespeare, William / 1564-1616; Vendetta; Youth; Italy / Verona; Adaptations; Ballet films; Dance films; Drama; Feature films; Fiction films; Film adaptations; Film; DVD-Video